Effectiveness of Afigel therapy in reducing urinary incontinence among premenopausal women: a quasi-experimental study in rural Indonesia - Siti Fatonah; Sulastri Sulastri (International Journal of Public Health Science (IJPHS), 2026)
Urinary incontinence (UI) affects millions globally, predominantly women, significantly impacting quality of life. This study evaluated Afigel as a novel intervention for reducing UI symptoms. A quasi-experimental pre-posttest design was employed with 93 premenopausal women randomly assigned to intervention (n = 31) and control (n = 62) groups. Data collection utilized personal data sheets, Afigel therapy standard operating procedures, observation sheets, and the questionnaire for urinary incontinence diagnosis (QUID). Dependent and independent t-tests analyzed the data. Among participants, 43% experienced stress incontinence, 47% experienced urge incontinence, and 10% mixed incontinence. Severity was mild (41%), moderate (45%), and severe (14%). The intervention group demonstrated a significant reduction in incontinence scores from 6.30 to 1.53 (p = 0.000), while the control group showed minimal change from 6.30 to 6.18 (p = 0.21). Afigel demonstrates potential as an effective UI management therapy. These findings suggest Afigel could substantially improve quality of life by reducing UI-related social embarrassment, activity limitations, and psychological distress. For primary health care settings, Afigel offers a potentially accessible, non-invasive treatment option that community health nurses and primary care providers could implement, reducing referral burdens on specialist services while addressing this prevalent yet often underreported condition.